2015
DOI: 10.1080/10962247.2015.1112316
|View full text |Cite
|
Sign up to set email alerts
|

Source apportionment of emissions from light-duty gasoline vehicles and other sources in the United States for ozone and particulate matter

Abstract: Following U.S. Tier 3 emissions and fuel sulfur standards for gasoline-fueled passenger cars and light trucks, these vehicles are expected to contribute less than 6% of the summertime mean daily maximum 8-hr ozone and less than 7% and 4% of the winter and summer mean 24-hr PM2.5 in the eastern U.S. in 2030. On days with elevated ozone or PM2.5 at four major urban areas, these vehicles contribute less than 7% of ozone and less than 5% of PM2.5, with sources outside North America and U.S. area source emissions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…29 CAMx was applied to a future summer month (July 2030) based on a scenario assuming nationwide adoption of the California Low Emission Vehicle (LEV) III standard with reduced gasoline sulfur. 23 This assumption for LDVs is similar to the Tier 3 standard proposed by the U.S. EPA. The modeling domain consists of a continental U.S. grid with 36 km horizontal grid resolution and a 12 km nested grid centered on the eastern U.S. (Figure 2).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…29 CAMx was applied to a future summer month (July 2030) based on a scenario assuming nationwide adoption of the California Low Emission Vehicle (LEV) III standard with reduced gasoline sulfur. 23 This assumption for LDVs is similar to the Tier 3 standard proposed by the U.S. EPA. The modeling domain consists of a continental U.S. grid with 36 km horizontal grid resolution and a 12 km nested grid centered on the eastern U.S. (Figure 2).…”
Section: Introductionmentioning
confidence: 84%
“…Our future-year scenario is one developed previously to study emission controls in 2030. 23 2. METHODS 2.1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The air quality impacts of potentially strengthening vehicle emission standards in SoCAB have been evaluated using atmospheric modeling . Similarly, several studies have evaluated the impacts associated with current and future California and U.S. vehicle emission regulations. However, these works generally consider the incremental reduction in emissions that future vehicles may have from current vehicleswhich are already relatively clean. The current work is distinguished from these efforts by demonstrating the fundamental change associated with nonregulated vehicles relative to the currently regulated vehicles as well as including all on-road vehicles in the LDV, MDV, and HDV sectors where LDV includes light-duty automobiles (LDA) and light-duty trucks (LDT).…”
Section: Introductionmentioning
confidence: 99%
“…Factors which may contribute to asthma exacerbations in north Texas include motor vehicle emissions and urban drilling. Motor vehicle emissions are major contributors to fine particulate matter air pollution (Kheirbek, Haney, Douglas, Ito, & Matte, ; Vijayaraghavan et al, ), and epidemiological studies have inferred the positive relationship between particulate air pollution and asthma symptoms (Munoz et al, ; Zhang, Craft, & Zhang, ). Previous research on children and adults has shown that residential proximity to major roadways or dense networks of roadways are significantly related to asthma symptoms (Gonzalez‐Barcala at al., ; Jacquemin et al, ) and on‐road exposure to air pollution is positively related to minority and lower socioeconomic status (Lindgren, Bjork, Stroh, & Jakobsson, ; Newman et al, ).…”
Section: Introductionmentioning
confidence: 99%